Lesson Study Sebagai Salah Satu Upaya Meningkatkan Kualitas Pembelajaran - Sumani Sumani (Jurnal Pendidikan, 2009)
Teaching is a complex act and there are many reasons lessons may work in one situation and not in another. In the instructional activities, the teachers too often try to begin with a lesson in mind instead of with goals in mind. Even with goals, they want to jump to the lesson before investigating the how the content develops and what prior knowledge students must have. Moreover, in some educational practice, many courses enroll students with a broad range of backgrounds, previous educational experiences, majors, interests, motivations as well as levels of important prior knowledge and skills. In many instances, this diversity often leads to various problems that need solutions. In this case, lesson study may be one of the alternative solutions. Base on this fenomenon, this study will serves a thorough discussion on: 1) the nature of lesson study, 2) the importance of lesson study, 3) the steps in lesson study, and 4) the development of lesson study.                                The analysis results in conclusions that 1) Lesson study, the primary form of professional development for Japanese teachers, is a teaching improvement activity in which instructors jointly develop, teach, observe, analyze and revise lessons for their courses. Lesson study teams build knowledge about how students learn in their discipline, produce a lesson that can be used by others, and create manuscripts for possible publication, presentation, and inclusion in teaching portfolios. The main goal of lesson study is continual improvement of teaching so that learners will learn more. Its primary focus is how students think and learn 2) Lesson study is one of the alternative solutions for the ineffective teaching activities. Lesson study systematically improves the instructional activities through collaborative inquiry. Moreover, there are some benefits can be taken from the lesson study: (a) The teachers can manage and administer the progress of their teaching activities, (b) They can get the valuable feetback from the other teachers, and (c) They can produce published scientific writing as the result of the implementation of the lesson study. 3) A lesson study cycle consists of  plan, do, check and act (PDCA). Plan is establishing the objectives and processes necessary to deliver results in accordance with the expected output. By making the expected output the focus, it differs from other techniques in that the completeness and accuracy of the specification is also part of the improvement. Do is mplementing the new processes, often on a small scale if possible. Check is measuring the new processes and compare the results against the expected results to ascertain any differences. Act is analyzing the differences to determine their cause. Each will be part of either one or more of the P-D-C-A steps.  4) The lesson study program can be developed in various ways.  It can be developed in the preservice or inservice training program for the teachers, and even it can be brought into the real classroom research activities, namely the classroom action research (CAR).             Lesson study changes us forever as a teacher.  The process of lesson study has been incredible. So much learning has taken place. Therefore, planning the lesson with such care and detail in the wording is so incredibly important.